2019
DOI: 10.21203/rs.2.9843/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epidemiologic relationship between periodontitis and type 2 diabetes mellitus

Abstract: ObjectivesTo systematically reviewing the epidemiologic relationship between periodontitis (PD) and type 2 diabetes mellitus (T2DM). Materials and MethodsFour electronic databases were searched up to December, 2018. Manual search including the reference lists of included studies and relevant journals. Observational studies evaluating the relationship between T2DM and PD were included. Meta-analyses were applied using STATA. ResultsA total of 53 observational studies were included. Pooled results of cross-secti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 31 publications
0
21
1
Order By: Relevance
“…In contrast to our findings, those of the most recent systematic review, which summarized observational studies exploring the bidirectional relationship between periodontal disease and diabetes, found that severe periodontitis increased the risk of type 2 diabetes by 53% (RR: 1.53; 95% CI: 1.27–1.83) (Wu et al, 2020). An earlier systematic review and meta‐analysis, which included six studies from 2013 to 2017 (most of which were conducted in Japan and Taiwan) also concluded that individuals with periodontal disease had a higher risk (adjusted hazard ratios ranged from 1.19 to 1.33) of developing diabetes compared to individuals with no periodontal disease (Graziani et al, 2018).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to our findings, those of the most recent systematic review, which summarized observational studies exploring the bidirectional relationship between periodontal disease and diabetes, found that severe periodontitis increased the risk of type 2 diabetes by 53% (RR: 1.53; 95% CI: 1.27–1.83) (Wu et al, 2020). An earlier systematic review and meta‐analysis, which included six studies from 2013 to 2017 (most of which were conducted in Japan and Taiwan) also concluded that individuals with periodontal disease had a higher risk (adjusted hazard ratios ranged from 1.19 to 1.33) of developing diabetes compared to individuals with no periodontal disease (Graziani et al, 2018).…”
Section: Discussioncontrasting
confidence: 99%
“…(RR: 1.53; 95% CI: 1.27-1.83) (Wu et al, 2020). An earlier systematic review and meta-analysis, which included six studies from 2013 to 2017 (most of which were conducted in Japan and Taiwan) also concluded that individuals with periodontal disease had a higher risk (adjusted hazard ratios ranged from 1.19 to 1.33) of developing diabetes compared to individuals with no periodontal disease (Graziani et al, 2018).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Diabetes was defined using ICD‐10 codes E10–E14, at least one claim per year with a prescription of anti‐diabetics for more than 30 days, or fasting glucose level ≥126 mg/dl from health screening. Follow‐up initiation was 1 year after the second screening, which was a wash‐out period to secure sufficient time from exposure to onset of diabetes and to minimize the prevalence of undiagnosed baseline diabetes (Wu et al, 2020). The follow‐up period lasted until the subject died or December 2013.…”
Section: Methodsmentioning
confidence: 99%
“…45 While the dental profession debates the impact of closer alignment with the larger healthcare environment, and whether the DMD better reflects that intent, there is ever-increasing evidence-based research on the oralsystemic connection and its significance for physical and mental health. For example, ongoing research in "periodontal medicine" indicates that oral infection and inflammation have been identified as risk factors for cardiovascular disease, 46 diabetes mellitus, 47 and other chronic diseases, much of which is being reported by esteemed journals of medicine, dentistry, and public health; for example, that conservative treatment of oral disease significantly reduces the cost of overall healthcare, particularly for inpatient/hospital utilization. 48 In general, the addition of selected primary healthcare activities in the dental office including possible monitoring and managing some chronic diseases such as diabetes will require greater use of mid-level providers.…”
Section: Implications Of Perceived Differences Between the Degrees Fo...mentioning
confidence: 99%